EFEKTIVITAS PELATIHAN PROGRAM MAHASISWA BIDANG TIK DALAM MENINGKATKAN KOMPETENSI CALON GURU PAI (Studi di Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga) - Muhammad Mustofa (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2018)
Abstract The Faculty of Tarbiyah and Teacher Training at UIN Sunan Kalijaga Yogyakarta held several pieces of training, both from Student Organizations and from their own faculties. With some training available at the faculty, the author needs to examine any training that is useful for PAI students of the Faculty of Tarbiyah and Teacher Training to become teachers later. Of the many existing pieces of training, one of which is the Interactive Learning Multimedia Lecture (Lectora Inspire) held by the Student Program for Information and Communication Technology at the Faculty of Tarbiyah and Teacher Training at Sunan Kalijaga State Islamic University in Yogyakarta. This article aims to find out the training held by the Information and Communication Technology Student Program. Abstrak Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta mengadakan beberapa pelatihan, baik itu dari Lembaga Kemahasiswaan (LKM) maupun dari fakultas sendiri. Dengan beberapa pelatihan yang ada di fakultas, maka penulis perlu meneliti pelatihan apa saja yang bermanfaat bagi mahasiswa PAI Fakultas Ilmu Tarbiyah dan Keguruan untuk menjadi guru nantinya. Dari banyaknya pelatihan-pelatihan yang ada, salah satunya adalah Pelatihan Multimedia Pembelajaran Interaktif (Lectore Inspire) yang diadakan oleh Program Mahasiswa Bidang Teknologi Informasi dan Komunikasi Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta. Artikel ini bertujuan untuk mengetahui pelatihan yang diadakan Program Mahasiswa Bidang Teknologi Informasi dan Komunikasi tersebut.